Pretreatment with water kefir reduces the development of acidified ethanol-induced gastric ulcers - Raiana Maria Prucoli Falsoni; Flavia de Souza Andrade Moraes; Mahira Sabino de Rezende; Cristiane Lyrio da Silva; Tadeu Uggere de Andrade; Girlandia Alexandre Brasil; Ewelyne Miranda de Lima (Universidade de São Paulo, 2022)
Abstract To evaluate the gastroprotective and antioxidant effects of pretreatment with water kefir on ulcers induced with HCl/ethanol. All pretreatments lasted 14 days. Male mice were separated into five groups: the control (C) group received vehicle without ulcer induction; the ulcerated (U) group received vehicle; the lansoprazole (L) group received 30 mg/kg/day lansoprazole; the water kefir (WK15 and WK30) groups received WK at a dose of 0.15 or 0.30 ml/kg/day, respectively. Gastroprotection was measured by ulcer area, ulcer index and ulcer reduction percentage. Antioxidant effects were quantified by measuring advanced oxidized protein products (AOPPs), superoxide dismutase (SOD), and catalase activity in the stomach. Pretreatment with WK at both doses promoted gastroprotection against HCl/ethanol-induced ulcers much like the pretreatment with lansoprazole. In addition, WK decreased protein oxidation while increasing SOD and catalase activity. We concluded that pretreatment with water kefir increases the activity of antioxidant enzymes, preventing gastric lesions induced by HCl/ethanol by maintaining the antioxidant performance in gastric tissue.